Pengaruh Linieritas Pendidikan dan Kompetensi Pedagogik Guru Terhadap Hasil Belajar Siswa SD di Kecamatan Bontoala Kota Makassar - Julsari Karopak; Muhammad Yunus; Sundari Hamid (Postgraduate Bosowa University, 2022)
Penelitian ini dilakukan dengan tujuan untuk mengetahuilinieritas pendidikan guru SD di Kecamatan Bontoala, kompetensi pedagogik guru SD di Kecamatan Bontoala, pengaruh linieritas pendidikan guru terhadap hasil belajar siswa SD di Kecamatan Bontoala, dan pengaruh kompetensi pedagogik guru terhadap hasil belajar siswa SD di Kecamatan Bontoala. Penelitian ini menggunakan penelitian kuantitatif yaitu menggunakan penelitian korelasional. Penelitian kuantitatif adalah sebuah penelitian dimana data penelitian yang dikumpulkan berbentuk angka-angka dan bermaksud menguji hipotesis yakni perbedaan linieritas pendidikan guru yang mengajar di SD Kecamatan Bontoala, perbedaan kompetensi antara guru yang berasal dari kependidikan dan non kependidikan di SD Kecamatan Bontoala, pengaruh linieritas pendidikan guru terhadap hasil belajar siswa SD di Kecamatan Bontoala, dan pengaruh positif dan signifikan kompetensi pedagogik guru terhadap hasil belajar siswa SD di Kecamatan Bontoala. Subjek dari penelitian ini adalah guru SD Kecamatan Bontoala Kota Makassar sebanyak 60 guru. Data dalam penelitian ini dikumpulkan dengan teknik kuesioner dan dokumentasi. Hasil penelitian yang diperoleh mengatakan bahwa terdapat pengaruh linieritas pendidikan guru terhadap hasil belajar siswa dan kompetensi pedagogik guru juga berpengaruh terhadap hasil belajar siswa SD di Kecamatan Bontoala Kota Makassar. Hasil uji t menunjukkan bahwa terdapat pengaruh linieritas pendidikan dan kompetensi pedagogik guru terhadap hasil belajar siswa. Melalui analisis regresi linier ganda dapat diketahui bahwa kedua variabel tersebut berpengaruh signifikan terhadap hasil belajar siswa. Dengan demikian linieritas pendidikan dan kompetensi pedagogik guru berpengaruh positif terhadap hasil belajar siswa di SD Kecamatan Bontoala Kota Makassar This research was conducted to know: (1) the linearity of teachers’ education in Elementary Schools in Bontoala District of Makassar, (2) the teachers’ academic competence in Elementary Schools in Bontoala District of Makassar (3) the influence of linearity of the teachers’ education to the learning outcomes in Elementary Schools In Bontoala District of Makassar, (4) the influence of teachers’ pedagogic competence to the learning outcomes in Elementary Schools in Bontoala District of Makassar. This research uses quantitative research that is correlational research. Quantitative research is a study of the data collected in the form of numbers and intends to test the hypotheses, namely the differences in the linearity of teachers’ education in Elementary Schools in Bontoala District of Makassar, the differences of teachers’ competence who are graduates of education and non-education majors in Elementary Schools in Bontoala District, the influence of linearity of teachers’ education to the learning outcomes of students in elementary school in Bontoala District, and the positive and significant influence of teachers’ pedagogic competence to the learning outcomes of the students in elementary schools in Bontoala District. The subjects of this research were 60 teachers in Elementary Schools in the Bontoala District of Makassar. The data in this research were collected using questionnaires and documentation techniques. The result of the data indicated that there was an influence of the linearity of teachers’ education and teachers’ pedagogic competence on the learning outcomes of the students in elementary schools in the Bontoala District. The t-test shows that the linearity of teachers’ education influenced the students’ outcomes in the Bontoala District of Makassar so that the teachers’ pedagogic competence. The result of multiple linear regression indicated that both teachers’ linearity of education and pedagogic competence significantly influenced the students’ outcomes. Thus, the linearity of education and teacher pedagogic competence has a positive effect on students’ learning outcomes in Elementary Schools In the Bontoala District of Makassar